External training demands in women's varsity rugby union players quantified by wearable microtechnology with individualized speed thresholds - Nyman, D. L. E.; Spriet, L. L. (The Journal of Strength and Conditioning Research, 2022)
This study used wearable Global Positioning System (GPS) microtechnology with individualized speed thresholds to examine external training demands in 29 female varsity rugby union athletes during competitive season practices. Players were categorized as forwards or backs and observed during fitness, game-based, or skill training days (FT/GT/ST). Global Positioning System-derived variables included distances, high-intensity running (HIR), work-to-rest ratio, power plays, and PlayerLoad. Five speed zones categorized athlete movements and were customized according to each individual's overall maximum velocity (Vmax). Compared with backs, forwards had lower overall Vmax (6.62 ± 0.66 m/s; 7.38 ± 0.61 m/s, p = 0.003) and HIR thresholds (3.97 ± 0.40 m/s; 4.43 ± 0.37 m/s, p = 0.003). There were no interaction effects between position and training day for any GPS-derived variables. However, there were several effects of position (p = 0.05), with forwards being lower than backs in mean Vmax, zone 1 distance, and power plays, and greater than backs in zone 3, zone 4, and HIR distances. Effects of the training day (p = 0.05) were also observed in zone 1 distance, with FT being lower than GT and ST, and in power plays, with FT being greater than ST. In female varsity rugby union athletes, there were significant positional differences in individualized speed thresholds and external training demands. However, there were few marked differences between fitness, game-based, and skill training days.